ANALISIS PELAKSANAAN PELAYANAN JASA EKSPEDISI DALAM MENGHADAPI PERSAINGAN BISNIS (Studi pada PT. Pos Indonesia (persero) Cabang Kota Lama Kecamatan Kuntodarussalam Kabupaten Rokan Hulu) - Kasmi Gusmita; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine how the implementation of expedition services in the face of business competition in PT. Pos Indonesia (persero) branch Kota Lama sub-district Kuntodarussalam regency Rokan Hulu. This research is motivated by the phenomenon of more and more companies enganged in the field of expedition or the like that have sprung up and there is still a lack of services provided by PT. Post of Indonesia (persero) branch Kota Lama sub-district Kuntodarussalam regency Rokan Hulu. In this study the Informants were taken as many as 5 respondents consisting of Key Informants namely the Head of Office and 4 suplementary informants namely the second staff and service users PT. Pos Indonesia (persero) branch Kota Lama. The technique used is Snowball Sampling Technique. The data in this study using the Triangulation method through interviews with consumers. Data obtained from the results of interviews with Key Informants were then cross-checked with complementary informants and then processed to be tested with qualitative methods. The results of the analysis using qualitative data analysis, because the data obtained in the form of information. The theory used in this study is Philip Kotler’s theory of the five characteristics of service delivery, namely reliability, responsiveness, cartainty, emphaty, tangiblity, showing the results the implementation of espedition service at PT. Pos Indonesia (persero) branch Kota Lama sub-district Kuntodarussalam regency Rokan Hulu already shows service and assignment of responsibilities that can be categorized as good, but there is a small portion of services that arre considered to be not optimal. In the face of business competition there are several efforts that can be made by PT. Pos Indonesia (persero) to achieve competitive advantage, especially in terms of service and service quality improvement contained in the theory of Fandy Tjiptono and Gregeorius chandra about service excellence, namely speed, hospitality, comfort, timeliness. Keywords: Services, Service Excellent, Business Competition, Qualitative Research